THE STRATEGIC ROLE OF GENERATIVE AI IN MANAGING COMPANY’S PROCESSES - Viorica Mirela ȘTEFAN-DUICU; Mihaela SUDACEVSCHI; Maria Zenovia GRIGORE (Challenges of the Knowledge Society, 2025)
This article focuses on the importance and the strategic role of generative artificial intelligence in process management at the organizational level and outlines the conceptual framework of generative AI technology. At a company level, decision-making processes are directly influenced by the automation of operational processes to a large extent, with human resource being the key to information modelling. The purpose of this paper is to highlight the impact and how generative AI technologies can be strategically leveraged within a company. These aspect concentrates on sustaining innovation at a high level and maintaining a competitive advantage in a dynamic economy. The main points of the research include: descriptive elements of AI technologies, exploration of generative AI capability in organizational environment processes, the strategic role of using these technologies, describing human resources in reshaping the results obtained and the conduct of work processes, identifying challenges and managing risks in this modern global framework of functioning in the human resources market. Generative AI technologies present a major potential in handling the company's business because it provides support on every operational level, being a strategic mechanism that facilitates adaptation to the innovative markets and resilient conditions.